Increased virulence of Italian infectious hematopoietic necrosis virus (IHNV) associated with the emergence of new strains. Issue 2 (8th June 2021) - Abbadi, Miriam; Gastaldelli, Michele; Pascoli, Francesco; Zamperin, Gianpiero; Buratin, Alessandra; Bedendo, Giulia; Toffan, Anna; Panzarin, Valentina
Abstract: Infectious hematopoietic necrosis virus (IHNV) is the causative agent of IHN triggering a systemic syndrome in salmonid fish. Although IHNV has always been associated with low levels of mortality in Italian trout farming industries, in the last years trout farmers have experienced severe disease outbreaks. However, the observed increasing virulence of IHNV is still based on empirical evidence due to the poor and often confounding information from the field. Virulence characterization of a selection of sixteen Italian isolates was performed through in vivo challenge of juvenile rainbow trout to confirm field evidence. The virulence of each strain was firstly described in terms of cumulative mortality and survival probability estimated by Kaplan–Meier curves. Furthermore, parametric survival models were applied to analyze the mortality rate profiles. Hence, it was possible to characterize the strain-specific mortality peaks and to relate their topology to virulence and mortality. Indeed, a positive correlation between maximum mortality probability and virulence was observed for all the strains. Results also indicate that more virulent is the strain, the earliest and narrowest is the mortality peak. Additionally, intra-host viral quantification determined in dead animals showed a significant correlation between viral replication and virulence. Whole-genome phylogeny conducted to determine whether there was a relation between virulence phenotype and IHNV genetics evidenced no clear clustering according to phenotype. Moreover, a root-to-tip analysis based on genetic distances and sampling date of Italian IHNV isolates highlighted a relevant temporal signal indicating an evolving nature of the virus, over time, with the more virulent strains being the more recent ones. This study provides the first systematic characterization of Italian IHNV's virulence. Overall results confirm field data and point out an abrupt increase in IHNV virulence, with strains from 2015–2019 showing moderate to high virulence in rainbow trout. Further investigations are needed in order to extensively clarify the relation between evolution and virulence of IHNV and investigate the genetic determinants of virulence of this viral species in rainbow trout.